Computer literacy of primary school teachers - Kiseliova, Orinta (Lietuvos matematikos rinkinys, 2003)
The research (sample N = 213) shows strong primary school teachers’ motivation to use computer technologies and dynamic vusual aids in teaching process. Today limited use of computers and lack of instruction programmes.